Women’s Death as the Triumph in the Patriarchal World of Victorian Imagination - Nikandam, Roya (Mediterranean Journal of Social Sciences, 2012)
The novel chosen for this study are Hardy’s Tess of the d’Urbervilles (1891) and the Mayor of Casterbridge (1889). Ichoose Lacan’s psychoanalytic theory as a way to understand the psyche or the unconscious of the Victorian construction ofgender. I will explore the process of the construction of the symbolic order. The close relation between Lacanian and feministtheories has led me to adopt the latter as well, as espoused by Julia Kristeva in order to investigate the interconnection of thesetheories through the manifestation of the woman’s role as goods. This manifestation refers to the ways in which the femalecharacters are victimized in the patriarchal order, which transforms them into commodities in what Lacan terms the symbolicmale-dominated setting. Therefore, it is crucial to study Kristeva’s discourse on the connection of women to abjection/death.Kristeva’s concept is considered under the postulation of Lacan’s psychoanalytic theories, to clarify the attempt of the patriarchalorder to repress the identities of women by depicting them as incomplete, and how they can contest this symbolic patriarchalview of the Victorian era. It will examine the paths that women have taken to overcome their oppressive exclusion that law andhow women can manifest their capability to threaten this order.